Early infantile epileptic encephalopathy due to biallelic pathogenic variants in PIGQ: Report of seven new subjects and review of the literature. Issue 6 (3rd August 2020) - Johnstone, Devon L.; Nguyen, Thi Tuyet Mai; Zambonin, Jessica; Kernohan, Kristin D.; St‐Denis, Anik; Baratang, Nissan V.; Hartley, Taila; Geraghty, Michael T.; Richer, Julie; Majewski, Jacek; Bareke, Eric; Guerin, Andrea; et al.
Abstract: We investigated seven children from six families to expand the phenotypic spectrum associated with an early infantile epileptic encephalopathy caused by biallelic pathogenic variants in the phosphatidylinositol glycan anchor biosynthesis class Q ( PIGQ ) gene. The affected children were all identified by clinical or research exome sequencing. Clinical data, including EEGs and MRIs, was comprehensively reviewed and flow cytometry and transfection experiments were performed to investigate PIGQ function. Pathogenic biallelic PIGQ variants were associated with increased mortality. Epileptic seizures, axial hypotonia, developmental delay and multiple congenital anomalies were consistently observed. Seizure onset occurred between 2.5 months and 7 months of age and varied from treatable seizures to recurrent episodes of status epilepticus. Gastrointestinal issues were common and severe, two affected individuals had midgut volvulus requiring surgical correction. Cardiac anomalies including arrythmias were observed. Flow cytometry using granulocytes and fibroblasts from affected individuals showed reduced expression of glycosylphosphatidylinositol (GPI)‐anchored proteins. Transfection of wildtype PIGQ cDNA into patient fibroblasts rescued this phenotype. We expand the phenotypic spectrum of PIGQ ‐related disease and provide the first functional evidence in human cells of defective GPI‐anchoring due to pathogenic variants in PIGQ.